Pelatihan Guru SD dalam Mengembangkan Pembelajaran Matematika Kontekstual Berbasis Wisata Edukasi melalui Math City Map di Taman Beregam, Musi Rawas - Drajat Friansah; Sukasno Sukasno; Yufitri Yanto; Zaqi Andre Alfian; Sindy Anjelina (LP4MK STKIP PGRI Lubuklinggau, 2025)
This community service aimed to improve elementary teachers’ competence in designing contextual mathematics learning using Math City Map at Taman Beregam, Musi Rawas. The two-day training covered preparation, implementation, and mentoring stages. Results indicated an increase in teachers’ understanding of contextual learning from 26% to 82%. Eleven out of fifteen participants (73.3%) successfully created contextual tasks integrating measurement, geometry, and ratio concepts with real park objects. Interview analysis revealed six main themes: learning transformation, technological innovation, adaptation challenges, implementation plans, institutional support, and teacher professionalism. The training effectively enhanced teachers’ innovative capacity in developing contextual, technology-supported mathematics learning.